2019
DOI: 10.3390/nu11051015
|View full text |Cite
|
Sign up to set email alerts
|

Fermented Cordyceps militaris Extract Prevents Hepatosteatosis and Adipocyte Hypertrophy in High Fat Diet-Fed Mice

Abstract: Nonalcoholic fatty liver diseases (NAFLD) is characterized by accumulation of lipid droplets in the liver. The objective of this study was to evaluate protective effects of fermented Cordyceps militaris extract by Pediococcus pentosaceus ON188 (ONE) against hepatosteatosis and obesity in mice fed a high-fat diet (HFD). Eight-week-old male C57BL/6J mice were fed HFD mixed with ONE for four weeks and its effects on hepatosteatosis and obesity were examined. Although ONE did not change food intake, it reduced bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…Hepatic steatosis, the first hallmark of NAFLD, is known to be characterized by excessive accumulation of lipid in hepatocytes [52]. Several previous studies have provided evidence regarding the hepatoprotective properties against HFD-induced NAFLD by reducing the liver damage markers and inhibiting the accumulation of lipid droplets in the liver tissues of HFD-fed rodents [53,54]. In parallel, our results demonstrated that ALM16 can exert protective effects and synergistic action against hepatic steatosis and liver injury in HFD-fed mice.…”
Section: Discussionsupporting
confidence: 76%
“…Hepatic steatosis, the first hallmark of NAFLD, is known to be characterized by excessive accumulation of lipid in hepatocytes [52]. Several previous studies have provided evidence regarding the hepatoprotective properties against HFD-induced NAFLD by reducing the liver damage markers and inhibiting the accumulation of lipid droplets in the liver tissues of HFD-fed rodents [53,54]. In parallel, our results demonstrated that ALM16 can exert protective effects and synergistic action against hepatic steatosis and liver injury in HFD-fed mice.…”
Section: Discussionsupporting
confidence: 76%
“…27 Resveratrol (Polygonum cuspidatum) and the extract from fermented Cordyceps militaris decrease the expression and activity of SREBP-1c and decrease fat synthesis. 28,29 Curcumin increases the phosphorylation of acetyl-CoA carboxylase (p-ACC) and decreases the ratelimiting enzyme acetyl-CoA carboxylase (ACC) of fatty acid synthesis, which inhibits lipogenesis. 30 Traditional Chinese medicine can also inhibit lipid synthesis and metabolism by activating AMPK.…”
Section: Inhibit Fat Production and Accumulationmentioning
confidence: 99%
“…The water extracts or polysaccharides of the Cordyces species have anti-hyperlipidemic effects in mice [ 10 13 ]. However, the lipid profile in mice is distinct from humans [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study already demonstrated that CM1 may improve HDL-mediated cholesterol efflux [ 17 ]. Recent studies also indicated that water-soluble components of Cordyceps species can lower hyperlipidemia [ 10 13 , 39 ]. This study suggested that CM1 is one of the water-soluble components with hypolipidemic effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation